Optimalisasi Pengereman Regeneratif dengan Perubahan Sudut Eksitasi pada Pulsa Tunggal - Kusumaningrum, Nazila; Riyadi, Slamet; Pratomo, Leonardus Heru; Setyawan, Florentinus Budi (Jurnal Teknik Elektro, 2021)
Most of the energy is wasted into heat energy due to conventional braking, so an optimal braking strategy is needed. A Regenerative braking utilizes the kinetic energy of the engine into electrical energy by changing the function of an electric machine into a generator. The regenerative braking system uses a Switched Reluctance Machine (SRM) which has several advantages; simple construction, does not require maintenance, and return energy to the battery. The method that can be used in the regenerative braking system of the SRM is the change of excitation angle to produce the maximum peak phase current. This study aims to optimize regenerative braking by changing the angle (θeks) using simple controls to produce energy that is greater than the battery voltage so that current may flow to the battery when braking occurs. The results of the analysis for method implementation were proven by testing the devices in the laboratory. Based on the results of the tests, the exact angle was obtained, namely the value of θeks = 20º and the value of θkom = 170º with an initial speed of 1822 RPM, reduced into 1522 RPM by braking process, which could produce a peak current of 12,5 A and a current flowing to the battery was 5A.